FIRST RECORDS OF AEDES TORMENTOR AND CULEX PANOCOSSA AS A RESULT OF VECTOR SURVEILLANCE ACTIVITIES CONDUCTED DURING THE CHARACTERIZATION OF FOCI OF EASTERN EQUINE ENCEPHALITIS IN TAMAULIPAS, MEXICO - Ortega-Morales, Aldo I.; Rodríguez-Pérez, Mario A.; Morales-Avitia, Isis J.; Flores-Salas, Guadalupe; Wei, Lihua; Solis-Hernández, MARIO; Rodríguez-Martínez, Luis M.; Estrada-Franco, José G.; Fernández-Santos, Nadia A. (Journal of the American Mosquito Control Association, 2024)
We report the 1st records of Aedes tormentor and Culex panocossa throughout vector surveillance events carried out in putative foci of eastern equine encephalitis in Tamaulipas, Mexico. Formerly, Ae. tormentor had been reported in, at least, 2 Central American countries and Mexico. In Mexico, reports were from the states of Campeche, Chiapas, Quintana Roo, and Veracruz. Records of Ae. tormentor in these 4 Neotropical states were recently reviewed and eliminated; thus, the southernmost geographic distribution for this species is considered to be the state of Tamaulipas Mexico in its neotropical zone. Further, Cx. panocossa had been collected in Guerrero, Tabasco, and Veracruz. In Tamaulipas, there are 82 species of mosquitoes, being the 4th state accounting for the highest mosquito species diversity of 11 states in which comprehensive studies have been conducted on the subject of mosquito distribution.